UTAUT2 MODEL EVALUATION OF ACCEPTANCE WEB-BASED MULTIMODALITY LEARNING MEDIA - Solihah, Dewi Siti; Abidin, Yunus; Kurniawan, Dede Trie (Universitas Pakuan, 2023)
In carrying out learning, teachers need a learning media. Along with advances in technology, teachers are required to be able to use technology-based learning media in learning. The purpose of this study is to determine the factors that influence the acceptability of web-based multimodality learning models in elementary school teachers using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The method used in this study is a quantitative method with a survey method using a questionnaire. Data processing was carried out using the PLS-SEM analysis technique. The research data was obtained from distributing questionnaires to 100 elementary school teachers. The results of this study indicate that the factors that influence teacher acceptance of web-based multimodality learning media are behavior intention, use behavior, performance expectancy, effort expectancy. ), social influence, facilitating conditions, hedonic motivation, price values, and habits. Based on the value of R Square, this web-based multimodality learning model is good for use in teaching in elementary schools.